Detection and molecular characterization of infectious bronchitis virus isolated from recent outbreaks in broiler flocks in Thailand - Pohuang, Tawatchai (The Korean Society of Veterinary Science, 2009)
Thirteen field isolates of infectious bronchitis virus (IBV) were isolated from broiler flocks in Thailand between January and June 2008. The 878-bp of the S1 gene covering a hypervariable region was amplified and sequenced. Phylogenetic analysis based on that region revealed that these viruses were separated into two groups (I and II). IBV isolates in group I were not related to other IBV strains published in the GenBank database. Group 1 nucleotide sequence identities were less than 85% and amino acid sequence identities less than 84% in common with IBVs published in the GenBank database. This group likely represents the strains indigenous to Thailand. The isolates in group II showed a close relationship with Chinese IBVs. They had nucleotide sequence identities of 97-98% and amino acid sequence identities 96-98% in common with Chinese IBVs (strain A2, SH and QXIBV). This finding indicated that the recent Thai IBVs evolved separately and at least two groups of viruses are circulating in Thailand.